Analisis Pelaksanaan Gerakan Literasi dalam Meningkatkan Minat Baca Siswa Kelas Tinggi di Sekolah Dasar - Apriliani Muharramah; Rosmalah Rosmalah; Adnan K Adnan K (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a type of descriptive qualitative research. The problem of this research is how to implement the school literacy movement, especially in increasing students' reading interest. This research is a type of descriptive qualitative research. The results showed that the implementation of the literacy movement was carried out through 3 stages, namely the habituation stage; conducting literacy mornings and structuring a literacy-rich environment. development stage; follow-up activities and library visits. learning stage; use strategies in reading activities. The obstacles faced are the lack of reading books, improving reading corners, and students who are not fluent in reading. Efforts are being made to coordinate with school principals to improve literacy facilities such as procuring books and revamping reading corners. The conclusion of this research is that the implementation of the literacy movement in increasing students' reading interest is carried out in three stages, namely the stages of habituation, development, and learning, but there are obstacles in terms of facilities. Efforts are being made to improve the facilities for supporting the school literacy movement